Cancer-Associated Fibroblasts Suppress Cancer Development: The Other Side of the Coin - Wang, Zhanhuai; Yang, Qi; Tan, Yinuo; Tang, Yang; Ye, Jun; Yuan, Bin; Yu, Wei (Frontiers in Cell and Developmental Biology, 2021)
Cancer-associated fibroblasts (CAFs) are the main stromal components of cancer, representing a group of heterogeneous cells. Many studies indicate that CAFs promote tumor development. Besides, evidence of the tumor suppression effects of CAFs keeps on merging. In the tumor microenvironment, multiple stimuli can activate fibroblasts. Notably, this does not necessarily mean the activated CAFs become strong tumor promoters immediately. The varying degree of CAFs activation makes quiescent CAFs, tumor-restrain CAFs, and tumor-promoting CAFs. Quiescent CAFs and tumor-restrain CAFs are more present in early-stage cancer, while comparatively, more tumor-promoting CAFs present in advanced-stage cancer. The underlying mechanism that balances tumor promotion or tumor inhibition effects of CAFs is mostly unknown. This review focus on the inhibitory effects of CAFs on cancer development. We describe the heterogeneous origin, markers, and metabolism in the CAFs population. Transgenetic mouse models that deplete CAFs or deplete CAFs activation signaling in the tumor stroma present direct evidence of CAFs protective effects against cancer. Moreover, we outline CAFs subpopulation, and CAFs derived soluble factors that act as a tumor suppressor. Single-cell RNA-sequencing on CAFs population provides us new insight to classify CAFs subsets. Understanding the full picture of CAFs will help translate CAFs biology from bench to bedside and develop new strategies to improve precision cancer therapy.